2023
DOI: 10.3390/coatings13010157
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on Collapsibility of Xi’an Loess Improved by Calcium Lignosulfonate

Abstract: To improve the problem of collapsibility of loess, adding industrial materials such as cement is common engineering treatment, but this seriously damages the reclamation performance of soil. Calcium lignosulfonate (CLS) from paper plant waste fluids is a natural bio-based polymer with good application prospects as a soil improver. In this paper, the collapsibility and mechanical properties of CLS improved loess were investigated using a collapsibility test, gray correlation analysis, and an unconfined compress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Problems in special areas where unknown factors exist can be solved, and it is widely used in disciplines such as agriculture, geology, and meteorology. Many researchers have successfully applied it to correlate the macroscopic properties and microstructure parameters of loess [ 16 , 17 , 18 , 19 ]. However, such analyses mainly focused on the mechanical strength of intact loess [ 20 , 21 ], while the correlation between soil’s shear strength index and its microstructural parameters under WD-FT coupled cycling has received much less attention.…”
Section: Introductionmentioning
confidence: 99%
“…Problems in special areas where unknown factors exist can be solved, and it is widely used in disciplines such as agriculture, geology, and meteorology. Many researchers have successfully applied it to correlate the macroscopic properties and microstructure parameters of loess [ 16 , 17 , 18 , 19 ]. However, such analyses mainly focused on the mechanical strength of intact loess [ 20 , 21 ], while the correlation between soil’s shear strength index and its microstructural parameters under WD-FT coupled cycling has received much less attention.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in recent years, many experts and scholars at home and abroad have used physical or chemical modification methods to study the engineering characteristics of adverse foundation soil 21 . Bai et al 22 used a collapsibility test, gray relational analysis, and unconfined compressive strength test to study calcium lignosulfonate-modified loess’s collapsibility and mechanical properties. Luo et al 23 conducted direct shear tests and unconfined compression tests by adding cement, polypropylene fibers, and loess samples of SCA-2 soil stabilizer composites and found that the compressive strength indexes of modified loess had a significant impact on foundation settlement.…”
Section: Introductionmentioning
confidence: 99%